Lower frequency of TLR9 variant associated with protection from breast cancer among African Americans. - Madison R Chandler; Kimberly S Keene; Johanna M Tuomela; Andres Forero-Torres; Renee Desmond; Katri S Vuopala; Kevin W Harris; Nancy D Merner; Katri S Selander (PLoS ONE)
Introduction Toll-like receptor 9 (TLR9) is an innate immune system DNA-receptor that regulates tumor invasion and immunity in vitro. Low tumor TLR9 expression has been associated with poor survival in Caucasian patients with triple negative breast cancer (TNBC). African American (AA) patients with TNBC have worse prognosis than Caucasians but whether this is due to differences in tumor biology remains controversial. We studied the prognostic significance of tumor Toll like receptor-9 (TLR9) protein expression among African American (AA) triple negative breast cancer (TNBC) patients. Germline TLR9 variants in European Americans (EAs) and AAs were investigated, to determine their contribution to AA breast cancer risk. Methods TLR9 expression was studied with immunohistochemistry in archival tumors. Exome Variant Server and The Cancer Genome Atlas were used to determine the genetic variation in the general EA and AA populations, and AA breast cancer cases. Minor allele frequencies (MAFs) were compared between EAs (n = 4300), AAs (n = 2203), and/or AA breast cancer cases (n = 131). Results Thirty-two TLR9 variants had a statistically significant MAF difference between general EAs and AAs. Twenty-one of them affect a CpG site. Rs352140, a variant previously associated with protection from breast cancer, is more common in EAs than AAs (p = 2.20E-16). EAs had more synonymous alleles, while AAs had more rare coding alleles. Similar analyses comparing AA breast cancer cases with AA controls did not reveal any variant class differences; however, three previously unreported TLR9 variants were associated with late onset breast cancer. Although not statistically significant, rs352140 was observed less frequently in AA cases compared to controls. Tumor TLR9 protein expression was not associated with prognosis. Conclusions Tumor TLR9 expression is not associated with prognosis in AA TNBC. Significant differences were detected in TLR9 variant MAFs between EAs and AAs. They may affect TLR9 expression and function. Rs352140, which may protect from breast cancer, is 1.6 X more common among EAs. These findings call for a detailed analysis of the contribution of TLR9 to breast cancer pathophysiology and health disparities.